Reactions of a Dioxidomolybdenum(VI) Complex with Thionation Reagents-Formation of Mo(IV) Species with Sulfur Donors - Salojärvi Esko; Peuronen Anssi; Sapkota Narhari; Lehtonen Ari (MDPI, 2022)
Molecular molybdenum complexes with sulfur donor ligands are generally studied as soluble model compounds for molybdenum enzymes essential for life. The dioxidomolybdenum(VI) complex with tetradentate aminobisphenolate ligand undergoes a reaction with thionation reagent P2S5 or its organic derivative, Lawesson's reagent, to yield stable Mo(IV) aminobisphenolate complexes, where pristine oxido ligands have been replaced by bidentate sulfur donors tetrasulfide, S-4(2-) or (4-methoxyphenyl)phosphonotrithioate residue derived from Lawesson's reagent. This is in contrast to the behaviour of analogous dioxidotungsten(VI) complex, which, under similar conditions, yields W(VI) S-2 systems. The overall cis,trans,cis geometry of the parent dioxidomolybdenum(VI) aminobisphenolate is retained, namely, the neutral nitrogen donors are in cis positions, phenolate oxygens are trans to each other and sulfur donors are cis. Although formally Mo(IV), thus d(2) system, the studied complexes have diamagnetic singlet electron configurations as a result of the axially compressed octahedral structures.